Auxetic Foam‐Based Contact‐Mode Triboelectric Nanogenerator with Highly Sensitive Self‐Powered Strain Sensing Capabilities to Monitor Human Body Movement. (15th May 2017) - Zhang, Steven L.; Lai, Ying‐Chih; He, Xu; Liu, Ruiyuan; Zi, Yunlong; Wang, Zhong Lin
Abstract : The first contact‐mode triboelectric self‐powered strain sensor using an auxetic polyurethane foam, conductive fabric, and polytetrafluroethylene (PTFE) is fabricated. Utilizing the auxetic properties of the polyurethane foam, the auxetic polyurethane foam would expand into the PTFE when the foam is stretched, causing contact electrification. Due to a larger contact area between the PTFE and the foam as the foam is stretched, this device can serve effectively as a strain sensor. The sensitivity of this method is explored, and this sensor has the highest sensitivity in all triboelectric nanogenerator devices that are used previously as a strain sensor. Different applications of this strain sensor are shown, and this sensor can be used as a human body monitoring system, self‐powered scale to measure weight, and a seat belt to measure body movements inside a car seat. Abstract : The first contact‐mode triboelectric self‐powered strain sensor is fabricated using auxetic materials. Utilizing the auxetic properties of polyurethane foam, the polyurethane foam will expand when it is stretched, causing contact electrification. Different applications are realized and the triboelectric self‐powered strain sensor can be used for monitoring human body movement.